Stoßwellenlithotripsie in Deutschland: Ergebnisse einer deutschlandweiten Umfrage = Shock wave lithotripsy in Germany : results of a nationwide survey - Schnabel, Marco Julius; Rassweiler, Jens (Der Urologe, 2015)
BackgroundFollowing its introduction in the 1980s extracorporeal shock wave lithotripsy (SWL) became the gold standard for therapy of ureteral and renal calculi. The research data published during the last decade suggest a paradigm shift to endourological techniques.ObjectivesThe purpose of this study was to compare whether the suggested loss of status for SWL corresponds with actual real-life treatment in Germany. A further aim was to assess the quality of SWL therapy in German hospitals.Materials and methodsThe board of the German Society for Shock Wave Lithotripsy (DGSWL) sent a questionnaire to 306 urological departments in Germany, which encompassed medical, technical and organizational topics in the therapy of ureteral and renal calculi. A total of 99 (33 %) questionnaires were returned.ConclusionWith the exception of a few departments, non-invasive SWL still plays a major role in the treatment of urolithiasis and a loss of the gold standard status is not in sight. The performance of SWL in German hospitals is carried out at a high level of quality. To maintain and optimize this status a structured SWL training and adherence to clinical practice guidelines are needed.